Al-Sahifa al-Sajjadiyya: A Study of the Pragmatic Dimension - djacem farih, djacem (El Omda in Linguistics and Discourse Analysis, 2018)
The Al-Sahifa al-Sajjadiyya of Ali ibn al-Husayn is considered a rich repository of knowledge and a document that embodies a comprehensive worldview, revealing many truths related to the relationship between الإنسان وربّه. It serves as a framework for defining the mechanisms through which human existence ought to be understood. The Sahifa is an encyclopedic work comprising supplications, intimate prayers, devotions, and elevated values. It has been called the “Psalms of the Household of Muhammad” due to the ethical principles, rights, duties, and refined manners it contains. It addresses both individual and societal concerns and provides a focal point for self-reflection by fostering a spiritual atmosphere. Its significance is further enhanced by the fact that it emerged during an era marked by severe turmoil and political conflicts that overshadowed the lives of Muslims, casting them into dark clouds devoid of the light, guidance, and radiance of Islam. Muslims had become preoccupied with sectarian and political alignments in pursuit of their interests and ambitions, leaving little trace of the spirituality, teachings, ethics, and wisdom of Islam. In this context, the Sahifa al-Sajjadiyya opened new horizons for religious awareness previously unfamiliar to المسلمين, as it called for devotion, purity of soul, and inner spiritual refinement.